Geoelectrical parameter measurements using an Asymmetrical Schlumberger Sounding technique in the southern part of the Dokan area, NE-Iraq - Amin, Abdulla K. (Contributions to Geophysics and Geodesy, 2026)
Fifteen Asymmetrical Vertical Electrical Sounding (AVES) points were acquired along three traverses extending in the southern Dokan area. The results are quantitatively interpreted through forward and inverse modelling to calculate Dar-Zarrouk parameters include transverse resistance (RT) and longitudinal conductance (SL) calculated from true resistivity (ρ), depth (d) and thickness (h) of sequence layers succession revealing aquifers from recent sediments overlying the upper part of the rhythmic cycle of the middle Tanjero Formation. Hydraulic parameters deduced from pumping test includes aquifer transmissivity (T) and hydraulic conductivity (K) calculated from equation K = T/h. Three relationships between the Dar-Zarrouk parameters and hydraulic parameters were established. Among these, the relationship between transmissivity (T) and transverse resistance (RT) shows the highest correlation coefficient (R2 = 0.9956), indicating that it is the most precise and reliable relationship. The derived equation (T = −0.0006 RT + 23.227) can therefore be used to estimate transmissivity directly from transverse resistance values for the studied area, as well as for nearby areas with similar geological conditions, where recent alluvial sediments overlie the Middle Tanjero Formation.